2013
DOI: 10.1186/1471-2229-13-48
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of Phosphate transporter 1 genes evolutionary divergence in Glycine maxL.

Abstract: BackgroundThe Phosphate transporter 1 (PHT1) gene family has crucial roles in phosphate uptake, translocation, remobilization, and optimization of metabolic processes using of Pi. Gene duplications expand the size of gene families, and subfunctionalization of paralog gene pairs is a predominant tendency after gene duplications. To date, experimental evidence for the evolutionary relationships among different paralog gene pairs of a given gene family in soybean is limited.ResultsAll potential Phosphate transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 90 publications
(142 reference statements)
1
38
1
5
Order By: Relevance
“…Interestingly, within some other plant species, such as in soybean, there exists specialized Pht1 member(s) that is (are) mainly expressed in sink tissues, such as in flowers, implying possible functions of these genes in Pi import from source to sink [13,71]. However, in our present study, we did not observe any member in the tomato Pht1 family that is dominantly expressed in the flower or fruit tissue.…”
Section: Discussioncontrasting
confidence: 72%
“…Interestingly, within some other plant species, such as in soybean, there exists specialized Pht1 member(s) that is (are) mainly expressed in sink tissues, such as in flowers, implying possible functions of these genes in Pi import from source to sink [13,71]. However, in our present study, we did not observe any member in the tomato Pht1 family that is dominantly expressed in the flower or fruit tissue.…”
Section: Discussioncontrasting
confidence: 72%
“…Thus, the differential expression together with the low Ka/Ks supports a possible subfunctionalization of these genes. Previous studies have shown that the prevalence of variable expression in soybean after polyploidization has revealed that several paralogous genes undergo subfunctionalization (Fan et al 2013;Roulin et al 2013). Accordingly, our results reinforce the theory of the retention of duplicate genes through subfunctionalization, which may constitute a transitional step to neofunctionalization (Roulin et al 2013).…”
Section: Synteny Analysis Demonstrates High Conservation Between the supporting
confidence: 89%
“…The Ka/Ks ratio generates insights into the processes that drive the changes at the molecular level. A Ka/Ks ratio >1 shows that neofunctionalization through positive selection acted during the sequence divergence, and a Ka/Ks ratio <1 suggests that subfunctionalization through negative selection operated during the divergence (Fan et al 2013;Zhang et al 2002).…”
Section: Synteny Analysis Demonstrates High Conservation Between the mentioning
confidence: 99%
“…Thus, understanding how plants acquire and utilize P i , and how low P i -tolerant plants thrive in harsh growing conditions, is critical to improving agricultural systems. In soybean, studies have characterized the expression pattern and role of genes important in model species P i homeostasis (Liao et al 2003;Qin et al 2012;Fan et al 2013;Song et al 2013;Li et al 2014;Yao et al 2014;Zhang et al 2014. Classical QTL studies have identified P i efficiency QTL in soybean (Liang et al 2010;Zhang et al 2009Zhang et al , 2014Zhang et al , 2017, one of which included RNA-seq analysis of two recombinant inbred lines (RILs) with contrasting tolerance to P i deficiency stress (-P i ).…”
Section: Introductionmentioning
confidence: 99%